2018
DOI: 10.1186/s12885-018-4228-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of tumor-infiltrating lymphocyte levels and the 21-gene recurrence score in ER-positive/HER2-negative breast cancer

Abstract: BackgroundRecent studies have shown that tumors with extensive tumor-infiltrating lymphocytes (TILs) have a higher probability of pathologic complete response, even in luminal/human epidermal growth factor 2 (HER2)-negative breast cancer. We compared TIL levels and the 21-gene recurrence score (RS) in estrogen receptor (ER)-positive/HER2-negative breast cancer.MethodsWe evaluated the percentage of stromal TILs in 198 ER-positive/HER2-negative patients in whom RS was obtained by examining slides of surgical spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
2
19
0
1
Order By: Relevance
“…The TIL score was evaluated as previously described [ 20 , 21 ]. A pathologist (YJC) blinded to the clinical information reviewed the histologic features using hematoxylin and eosin (H&E) staining.…”
Section: Methodsmentioning
confidence: 99%
“…The TIL score was evaluated as previously described [ 20 , 21 ]. A pathologist (YJC) blinded to the clinical information reviewed the histologic features using hematoxylin and eosin (H&E) staining.…”
Section: Methodsmentioning
confidence: 99%
“…TNBC was defined by the lack of ER, PR and HER2 based on immunohistochemical (IHC) stain. For routine IHC studies, ER (1:100 clone 6F11; Novocastra, Newcastle upon Tyne, UK), PR (clone 16; Novocastra), HER2 (4B5 rabbit monoclonal antibody; Ventana Medical Systems, Tucson, AZ, USA), and Ki-67 (MIB-1; Dako, Glostrup, Denmark) were stained using formalin-fixed paraffin-embedded tissue sections as previously described [13,14]. ER positivity and PR expression on immunohistochemistry were defined according to the modified Allred system.…”
Section: Patients and Tumor Samplesmentioning
confidence: 99%
“…Although the RT-PCR results have been shown to be highly concordant with the results of IHC/fluorescent in situ hybridization (FISH) assays [ 26 , 27 ], the potential variability in RS values between CNBs and resection specimens is multifactorial and can be affected by single-gene expression, tumour heterogeneity and pre-analytic differences such as the delay to fixation, duration of fixation, or differences in fixatives. Furthermore, it has been reported that the presence of increased stromal cellularity and/or associated inflammatory cells and tumour-infiltrating lymphocytes (TILs) may contribute to an apparently increased recurrence risk according to the 21-gene assay [ 28 , 29 ]. Consequently, in this study, we assessed the ER, PR, HER-2 and Ki-67 status and RS value in paired CNBs and resection specimens from 50 BC patients.…”
Section: Introductionmentioning
confidence: 99%